Pharmacological modulation of activation-secretion of rat serosal mast cells by chymase, an endogenous secretory granule protease. - Schick, B (1985)
The action of pharmacologic agents on chymase-induced exocytosis of beta-hexosaminidase and arachidonic acid (AA) metabolism by rat serosal mast cells (RSMC) was determined and compared with their effects on anti-IgE induced activation. Indomethacin (INDO) (less than or equal to 10 microM), a cyclooxygenase inhibitor, did not affect chymase- or anti-IgE-mediated exocytosis, while completely inhibiting prostaglandin D2 (PGD2) release at 1.25 microM. Theophylline (THEO), mepacrine, 3-amino-1-[m-(trifluoromethyl)-phenyl]-2-pyrazoline (BW755C), and diethylcarbamazine (DEC), inhibitors of adenosine binding and phosphodiesterases, phospholipases, AA metabolism, and vesicular transport as well as leukotriene A4 formation, respectively, inhibited exocytosis with ID50 values of 3.4, 0.22, 3.4 and 1.9 mM for chymase and 2.4, 0.17, 2.8 and 5.2 mM for anti-IgE. These agents inhibited net PGD2 release with ID50 values of 2.1, 0.04, less than 0.05, and 1.5 mM for chymase and of 0.5, 0.1, less than 0.05, and 4 mM for anti-IgE. 5,6-Dehydroarachidonic acid (DHA) and arachidonyl hydroxylamine (AH), 5-lipoxygenase inhibitors, did not affect chymase-mediated exocytosis; anti-IgE-mediated exocytosis was not altered by AH but was suppressed by DHA (ID50 = 20 microM). Nordihydroguaiaretic acid (NDGA), an antioxidant, inhibited chymase-mediated exocytosis dose-dependently (ID50 less than or equal to 13.3 microM) while decreasing anti-IgE-mediated exocytosis by only 30% at 2.5-20 microM; net PGD2 release induced by both stimuli was inhibited dose-dependently. 2',5'-Dideoxyadenosine (DDA) and 1,6-di(0-(carbamoyl)cyclohexanone oxime)hexane (RHC 80267) and inhibitors of adenylate cyclase and of di-triglyceride lipases, respectively, had little effect on exocytosis induced by chymase but inhibited that induced by anti-IgE with ID50 values of 0.4 mM and 37 microM, respectively. With DDA the inhibition of net PGD2 release occurred with anti-IgE but not chymase, whereas RHC 80267 inhibited both chymase and anti-IgE-mediated PGD2 release. Differential inhibition of activation-secretion suggests either that chymase provides a step inhibited in IgE-mediated exocytosis by DDA, RHC 80267 and DHA, or that the activating pathway initiated by chymase is distinct.